ABOUT THE ROLE OF LIBERAL EDUCATION IN UNIVERSITY’S INNOVATION ACTIVITY - Pavel N. Ermakov; Irina V. Abakumova (Высшее образование в России, 2016)
The article focuses on the development of the conception of liberal education at the university inthe context of its innovation activity. The authors suggest a new didactic interpretation of two basic ideas of modernization – humanization and humanitarization of education. There are described the main lines of “humanitarian” transformation of the learning process, and the priority goals and tasks are marked out. The authors assert that the university should not only provide a student with the assets of knowledge but also give him an impetus for self-development and successful professional self-realization.